Poland’s European Policy 2015–2019 in the Perspective of Liberal Intergovernmentalism - Piotr Tosiek (Facta Simonidis)
The purpose of this article is to evaluate Poland’s European policy during the first term of the Law and Justice party government (2015–2019) in terms of participation in the general debate on the future of the EU. The theoretical background is the liberal intergovernmentalism, and the main thought is the statement that in the analyzed years Poland pursued a policy that did not take into account the basic assumptions of liberal intergovernmentalism treated normatively. The Polish authorities did not present concepts consistent with the internal Polish “community of views”, and when selecting partners and negotiating methods, they pursued an ideological policy, focusing on one partner with little potential. Despite these shortcomings, it was possible to maintain the shape of the institutions and procedures dominating in the EU favorable from the point of view of Poland’s pragmatically understood interests. Poland’s non-confrontational attitude to day-to-day politics also played a positive role here.